2009
DOI: 10.1093/scan/nsp037
|View full text |Cite
|
Sign up to set email alerts
|

The shared signal hypothesis and neural responses to expressions and gaze in infants and adults

Abstract: Event-related potentials were recorded from adults and 4-month-old infants while they watched pictures of faces that varied in emotional expression (happy and fearful) and in gaze direction (direct or averted). Results indicate that emotional expression is temporally independent of gaze direction processing at early stages of processing, and only become integrated at later latencies. Facial expressions affected the face-sensitive ERP components in both adults (N170) and infants (N290 and P400), while gaze dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
46
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 32 publications
16
46
2
Order By: Relevance
“…The activation of the amygdala while observers perceived bodily expressions of anger replicates previous studies (Pichon et al, 2009) and supports its proposed role in the automatic detection of threat (Emery and Amaral, 2000;LeDoux, 2000;Amaral et al, 2003;Feinstein et al, 2011). Amygdala damage diminishes the brain's response to threatening faces at both the ϳ100 -150 and ϳ500 -600 ms time ranges (Rotshtein et al, 2010), and, in both infants and adults, the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). Furthermore, previous fMRI studies manipulating self-involvement during face perception revealed that facial expression and gaze direction are integrated in the medial temporal poles (Schilbach et al, 2006;Conty and Grèzes, 2012) or in amygdala (Adams and Kleck, 2003;Hadjikhani et al, 2008;NЈDiaye et al, 2009;Sato et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The activation of the amygdala while observers perceived bodily expressions of anger replicates previous studies (Pichon et al, 2009) and supports its proposed role in the automatic detection of threat (Emery and Amaral, 2000;LeDoux, 2000;Amaral et al, 2003;Feinstein et al, 2011). Amygdala damage diminishes the brain's response to threatening faces at both the ϳ100 -150 and ϳ500 -600 ms time ranges (Rotshtein et al, 2010), and, in both infants and adults, the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). Furthermore, previous fMRI studies manipulating self-involvement during face perception revealed that facial expression and gaze direction are integrated in the medial temporal poles (Schilbach et al, 2006;Conty and Grèzes, 2012) or in amygdala (Adams and Kleck, 2003;Hadjikhani et al, 2008;NЈDiaye et al, 2009;Sato et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations